Educators Of Young Workers Who Study: Learning to Teach - Analise de Jesus Da Silva (Arizona State University, 2013)
The projects analyzed in this article were done in 2010 and 2011, along with the participation of young learners from YAE (Youth and Adults Education) whose age is between 15 and 29 years old, as an activity of the subject coursed by their teachers during the accomplishment of the Post-Graduate Specialization in Teaching Sensu Lato of YAE in Basic Education: Youth Attending the YAE, for two semesters. It was observed the success of the Action Projects with regard to various aspects evaluated during its planning and execution, as follows: promoting learning beyond the classroom; the perception of the importance to perform group activities, building study groups and applying what was learnt in workshops, both in the construction, production and use of technological resources as in the solidary economy; promoting the appropriation of cultural property, offered by counties and state, by young learners with consequent awareness that this access is a right for all; and,  in special, fostering to the interest of the learners for the school activities in order to make them feel co-responsible for their learning. As the result it is seen no temporary school dropouts and a 37% reduction in the number of sporadic absences by students of the Specialization Course. A reflection on the educational activities addressed in this article is the result of a compilation of nine projects developed in a course focusing on youths present in the YAE. This effort is subjected to a liberating theoretical and methodological approach, according to the searched principles, especially at Paulo Freire, which gives it academic rigor and quality. It was observed, in the daily practice the dialogue between the projects reported in interface with a theoretical foundation able to explain the theoretical- epistemic advances to the field of Education for Youths and Adults.